Using the Lecturer’s Training Site with a Conscious Approach to Learning Russian as a Foreign Language - S. V. Marchuk (Открытое образование (Москва), 2020)
The purpose of the research is to demonstrate the productivity of using the lecturer’s training web-site of Russian as a foreign language in the preparatory courses at the University. Lecturer’s training website is an effective means stipulated with principal of consciousness and activity of scholars under the guidance of a lecturer. Training web-site as informative and communicative instrument is able to combine didactic matter, learning techniques and methods for different forms of work organization: full-time, mixed and distance; also, didactic material means educational complexes, information and communication means, control and training. An important principle underlying the proposed teaching method is the refusal to use the methods of unconscious repetition.Materials and methods. To identify the ef fectiveness in application of lecturer’s training web-site various educational platforms were used having different target and national groups. The analysis of studies on mechanical repetitions of well-known physiologists, biologists, lecturers was carried out, which allowed us to come to the conclusion about the ineffectiveness of using techniques with unconscious repetitions in the educational process. Systematic use of lecturer’s web-site in educational process shows that most effective methods and techniques are audio-visual, textual exercises from simple to complex with further audio dubbing, audio method of teaching phonetics and literacy, “lively dialogue” as a new technique in teaching Russian for foreigners, vocabulary works and differentiated approach. Observation, comparison and matching methods were applied, which helped to identify the productivity of learning with the use of multimedia. To identify scientific novelty, an empirical method was used by introducing author’s personal educational web-site project www.russian-teacher.ru with a description of observations and summarizing the results.Results. It is noted that the offered website format is innovation in the field of teaching Russian for foreigners during preparatory course. It was proved with high positive result that the use of a lecturer’s personal training website with the possibility of feedback gives good results when teaching Russian as a foreign language in a short time  at the nonlinguistic university during the period of distance learning, with a mixed form of education.Conclusion. Research using the site continues in different groups by nationality (it is possible that there are several linguistic ones), by the number (it is possible to train a group of up to 15 people), by the degree of preparation (possibly A1-B1). The site has a number of advantages: the ability to edit as needed, change the interface and generate content. The study shows how didactics is interconnected with physiology, and the lecturer’s competence includes creativity, which in modern informational conditions is considered through the use of multimedia the lecturer’s training personal website www. russian-teacher.ru.